2020
DOI: 10.1029/2020ja028056
|View full text |Cite
|
Sign up to set email alerts
|

Mars Express Observations of Cold Plasma Structures in the Martian Magnetotail

Abstract: We present observations from five Mars Express (MEX) orbits in September 2016 while the spacecraft passed through the Martian induced magnetotail at altitudes up to 3,500 km. On these orbits, the Mars Advanced Radar for Subsurface and Ionosphere Sounding (MARSIS) instrument was operated in Active Ionospheric Sounding (AIS) mode at much higher altitude than normal, acting as a local sounder and detecting cold plasma structures in this region. In this paper we combine MARSIS tail measurements with solar wind dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…Of more relevance here is the preceding local minimum in plasma density that is observed in case of VGAM1 in Figure 8a, approximately 8 hr prior to closest approach, at distances of ∼55 R V down-tail, suggestive of the spacecraft moving at least partially in toward the Venus plasma wake formed toward the center of the induced magnetotail. However, that an extended but nevertheless constrained plasma structure, having a local maximum along the spacecraft trajectory, is then found tailward of this wake encounter in both VGAM1 and VGAM2 could be evidence of some detached escaping plasma structure, as has been found, for example, at Mars (Brain et al, 2010;Stergiopoulou et al, 2020), Titan (Coates et al, 2012;Edberg, Gren, et al, 2011) and previously at Venus (Brace et al, 1982;Collinson et al, 2022), albeit at closer distances. An interesting follow-up study could be a comparison with similar observations during solar maximum to see in what way the solar cycle may affect these plasma structures and if there is a correlation with the observed decrease of the escape rates of H + and O + during solar maximum (Persson et al, 2018).…”
Section: Discussionsupporting
confidence: 60%
“…Of more relevance here is the preceding local minimum in plasma density that is observed in case of VGAM1 in Figure 8a, approximately 8 hr prior to closest approach, at distances of ∼55 R V down-tail, suggestive of the spacecraft moving at least partially in toward the Venus plasma wake formed toward the center of the induced magnetotail. However, that an extended but nevertheless constrained plasma structure, having a local maximum along the spacecraft trajectory, is then found tailward of this wake encounter in both VGAM1 and VGAM2 could be evidence of some detached escaping plasma structure, as has been found, for example, at Mars (Brain et al, 2010;Stergiopoulou et al, 2020), Titan (Coates et al, 2012;Edberg, Gren, et al, 2011) and previously at Venus (Brace et al, 1982;Collinson et al, 2022), albeit at closer distances. An interesting follow-up study could be a comparison with similar observations during solar maximum to see in what way the solar cycle may affect these plasma structures and if there is a correlation with the observed decrease of the escape rates of H + and O + during solar maximum (Persson et al, 2018).…”
Section: Discussionsupporting
confidence: 60%
“…Recently, using the ionosphere sounding radar measurements on Mars Express, Stergiopoulou et al. (2020) have observed isolated cold plasma structures at much higher altitude than normal. The authors also could not find a relation of these structures to a sole driver.…”
Section: Discussionmentioning
confidence: 99%
“…A high solar irradiance is also favorable for initiation of very high ion fluxes but there are also other unknown yet causes responsible for the maximum values. Recently, using the ionosphere sounding radar measurements on Mars Express, Stergiopoulou et al (2020) have observed isolated cold plasma structures at much higher altitude than normal. The authors also could not find a relation of these structures to a sole driver.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we select data where the MARSIS lower frequency used on the nightside is typically 1.8–3 MHz, and 4–5 MHz on the dayside, depending upon the planned operations. The MARSIS SubSurface mode typically operates for 15 min either side of the spacecraft periapsis, which has varied from 275 to 350 km during the mission, a limited portion of the seven‐hour orbital period (e.g., Stergiopoulou et al., 2020). Further, the radar is not operated on every orbit to accommodate the operation of other instruments.…”
Section: Data Sets and Selectionmentioning
confidence: 99%